Redes Culturais nos Primórdios da Europa: 2400 Anos da Fundação da Academia de Platão - Carmen Soares (Humanitas Supplementum, 2016)
By celebrating the 2400th anniversary of the founding of Plato's Academy, this book gathers ten contributions concerning the founder of the Academy, his school and work, as well as the influence Plato exerted on later authors (from antiquity to the present), and the reception of his legacy throughout history.The themes explored in the five initial chapters focus on the analysis of various topics treated in individual Pla -tonic dialogues. To begin, the Phaedrusis considered for its significance regarding the philosophical conception of a "supra-heavenly place". The next two chapters reflect upon Platonic paideia, first on the pedagogical princi-ples of The Statesman, and next on the analysis of sports activities in The Republic and inThe Laws. The dramatic and philosophical implications arising out of the multicultural origins of the characters in The Laws are brought into perspective alongside an insight drawn from the banquet, considered a model on which a philosophic com-munity can be constituted. The five remaining chapters have a general focus on Plato's presence in later authors (from Neoplatonism to contemporary literature), as well the influence of the Academy.